ACESSIBILIDADE DA PESSOA COM DEFICIÊNCIA AO CARGO DE SOLDADO DA POLÍCIA MILITAR: uma análise do concurso da Polícia Militar do Maranhão realizado em 2017. - BORCHARTT, Priscilla Karenwen Oliveira Rocha (2021)
The Law nº 8.213 / 1991, also known as “Quota Law”, establishes in article 93, that companies that have more than 100 (one hundred) employees must allocate a percentage of their vacancies for people with disabilities. In public contest, in turn, should also observe this rule, present in Decree nº. 9.508, of September 24th, 2018, art. 1º. Also, the organizing jury of the contest must reserve a part of their vacancies for people with disabilities, that includes police contest. One of the stages of the contest for this public position to be a Police is the Physical Ability Test (“TAF”), which happens as the same way for all the candidates, without any adaptation. In view of this, the problem proposed in this research focuses around the question: "The corporation of the Maranhão Military Police observes the principle of equal access, specifically, the concept of factual equality defended by Robert Alexy (2008), in his work ‘A Theory of Constitucional Rights’, in the execution of their public tenders, in relation to candidates who compete as a person with a disability? ”. Therefore, it will be used as an object of this work the Public Civil Action nº 0812209-82.2018.8.10.0001, which resulted from the contest of Military Police of Maranhão, held in 2017. The methodological approach used for this work was the hypotheticaldeductive method, with technical bibliographic and documentary. It seeks to understand the processual construction of the Public Civil Action, highlighting the arguments presented by authors and defendant, also as a highlight or process of construction of the arguments presents in the sentence, as a baseline of framework it used the method of content analysis.